ECtHR: ZUREK v. POLAND (Application No. 39650/18,16 June 2022): Constitutional Crisis and the Judge's Freedomof Expression - Wojtanowski, Mateusz (2023)
The article is devoted to the analysis of the judge's freedom of expression in a constitutional crisis, using the ECtHR case of Zurek v. Poland as an illustration. The argument begins with a discussion of the facts of the case and the judgment. At this point, I argue that the category of discriminatory legalism is relevant to the facts of the case. Further, two interrelated problems are addressed, which are considered to be particularly relevant for the expression of the judge in the course of the constitutional crisis. These are: 1) the relevance of Article 10 in relation to speaking in one's professional (here: judicial) capacity, and 2) an attempt to determine whether the judge's opposition to a constitutional crisis is an exercise of his or her freedom or a duty. On both issues, I also present the position of Judge Wojtyczek, who challenged the majority views in his separate opinion (partly dissenting, partly concurring). I believe that the disagreement between Wojtyczek and the majority goes to fundamental philosophical-legal issues and can be described as a friction between the analytical and post-analytical approaches to law.
Keywords: Freedom of Expression of a Judge; Constitutional Crisis; Human Rights; ECtHR; Post-analytical Philosophy; Legal modalities